EFFECTIVENESS OF ANTIOXIDANT PSIDIUM GUAJAVA L LEAF EXTRACT TO MINOR TYPE RECURRENT STOMATITIS AFTOSA (RAS): EFEKTIVITAS ANTIOKSIDAN EKSTRAK DAUN PSIDIUM GUAJAVA L TERHADAP STOMATITIS AFTOSA REKUREN (SAR) TIPE MINOR - Darwis, Aida Fadhilla; Rosidah; Wilda H. Lubis (Dentika: Dental Journal, 2016)
Minor Recurrent Athous Stomatitis (RAS), known as sore that often occurs in oral disease. That characterized by ulcers and pain symptoms for 3-10 days which disrupt the activities that prompt patients seeking medication to relieve these symptoms. RAS etiology is not known clearly, some studies associate it with free radicals. Guava leaves/ Psidium guajava L have much content of bioactive component that are efficacious as analgesic, anti-inflammatory, antimicrobial / antidiarrheal, hepatoprotective and antioxidant. The purpose of this study to determine the effectiveness of antioxidant leaves of Psidium guajava L against Minor RAS by reduction of the diameter of ulcers and pain. This clinical trial was carried out using a single-blind randomized pretest posttest control group method. That consisted of 30 participants who had minor RAS with 15 people got extract gel Psidium guajava L 3% as a treatment group and 15 others received placebo (basic gel) as a control group. Ethanol extract was obtained by maceration method and antioxidant activity test by DPPH (dipheniyl picrylhidrazil) method. This study shows the results of the ethanol extract of leaves of Psidium guajava L has a very strong antioxidant activity with IC50 value of 22.39 ppm. Gel extracts give a a meaningful effect on the healing SAR with statistically significant in the reduction of ulcers diameter p 0.007 by repeated Annova test and a reduction in pain scores p <0.001 by Friedman test. In conclusion, extract Psidium guajava Linn leaves as a high antioxidant content effective promotion the healing process by reduced diameter ulcer and pain of Minor SAR.